Effect of different corrective force directions applied by spinal orthoses on the patients with adolescent idiopathic scoliosis - Hui-Dong Wu; Chang-Liang Luo; Chen He; Lu Li; Winnie Chiu-Wing Chu; Wei Liu; Man-Sang Wong (BMC Musculoskeletal Disorders)
Abstract Background Spinal orthoses are commonly prescribed for adolescent idiopathic scoliosis (AIS), yet their three-dimensional correction was not fully understood. The amount of deformity control largely depends on the corrective forces applied, which remain empirically based due to a lack of consensus on optimal force application. This study investigated the effects of different corrective force directions exerted by spinal orthoses on patients with AIS. Methods A retrospective analysis was conducted on 78 subjects. The trunk was segmented into four quadrants using coronal and sagittal planes from a top-down perspective. Each left or right posterolateral quadrant (with 90°) was further subdivided into zones 1–4, from the sagittal to coronal planes. Based on the zone where the resultant corrective force direction fell, the subjects were categorized into Group 1 (zone 1), Group 2 (zone 2), Group 3 (zone 3), or Group 4 (zone 4). The direction of the corrective force was estimated using modified models of the subjects’ bodies, designed through a computer-aided design and manufacturing system integral to the orthosis fabrication process. The effects of corrective forces in different zones on scoliotic spine were assessed. Results Among the subjects, 3 were in Group 1, 17 in Group 2, 52 in Group 3, and 6 in Group 4. Due to the limited number of subjects, data from Groups 1 and 4 were not analysed. Groups 2 and 3 showed significant reductions in Cobb angle in the coronal plane and plane of maximum curvature (PMC) following orthosis fitting (p < 0.05). Group 2 displayed a significant decrease > 5º in thoracic kyphosis (p < 0.05). Both Groups 2 and 3 exhibited significant reductions in lumbar lordosis. PMC orientation remained unchanged over time (p > 0.05) but was notably higher in Group 2 after orthosis fitting (p < 0.05). Conclusions Corrective forces applied by spinal orthoses in zones 2 and 3 effectively controlled lateral curve progression. Notably, only forces in zone 3 neither significantly reduced thoracic kyphosis nor exacerbated the deviation of scoliotic spine from the sagittal plane. Further research is needed to validate and expand upon these results.